2019
DOI: 10.5551/jat.48553
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Cerebral Small Vessel Disease on 7T Magnetic Resonance Imaging in Familial Hypercholesterolemia

Abstract: Aim: It remains unclear whether elevated low-density lipoprotein cholesterol (LDL-C) is a risk factor for cerebral vascular disease. Familial hypercholesterolemia (FH) is the most appropriate model for understanding the effects of excess LDL-C because affected individuals have inherently high levels of circulating LDL-C. To clarify the effects of hypercholesterolemia on cerebral small vessel disease (SVD), we investigated cerebrovascular damage in detail due to elevated LDL-C using high resolution brain magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…By contrast, in a Chinese cohort of 4683 hospitalized subjects plasma low density lipoprotein (LDL) cholesterol was associated with an increased burden of WMH (58). This is consistent with the recent finding that subjects affected by familial hypercholesterolemia have an increased burden of WMH when compared to healthy controls (59). A recent trial on 732 hypertensive individuals has shown a significant reduction in WMH progression in subjects assigned to treatment with Rosuvastatin (60).…”
Section: Hypercholesterolemiasupporting
confidence: 79%
“…By contrast, in a Chinese cohort of 4683 hospitalized subjects plasma low density lipoprotein (LDL) cholesterol was associated with an increased burden of WMH (58). This is consistent with the recent finding that subjects affected by familial hypercholesterolemia have an increased burden of WMH when compared to healthy controls (59). A recent trial on 732 hypertensive individuals has shown a significant reduction in WMH progression in subjects assigned to treatment with Rosuvastatin (60).…”
Section: Hypercholesterolemiasupporting
confidence: 79%
“…Therefore, the necrotic core is likely to facilitate progressive plaques and complications such as IPH 19) . Elevated LDL cholesterol can affect the pathologic progression of various blood vessels, including large arteries and microcirculation 20) . It is possible to stop plaque progression if active treatments, such as statins, are administered to patients 21) .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we carried out a stratified analysis by hypertension status and sex. All analyses were performed with adjustment for age, sex, and mean arterial pressure (Model 1) and controlled for other covariates, including smoking status, current use of antihypertensive medicines, body mass index, diabetes, and hyperlipidemia 22 , 23 ) (Model 2). Receiver operating characteristic curve analysis was applied to determine the optimal cut-off values of extracranial artery indictors for discriminating the presence or absence of CSVD.…”
Section: Methodsmentioning
confidence: 99%